GAMBARAN POLA PEMBERIAN MAKAN PADA BALITA USIA 2-5 TAHUN DI KECAMATAN BAITURRAHMAN KOTA BANDA ACEH - Az-zahra, Indah; Hartaty, Neti; Putri , Suraya (Information Technology and Science (ITScience), 2025)
Improper feeding patterns in toddlers can lead to health issues, decreased immunity, and an increased risk of long-term cognitive developmental disorders. This study aimed to describe the feeding patterns of children aged 2-5 years in the Baiturrahman District of Banda Aceh city. The study employed a quantitative design with a cross-sectional approach. A sample of 100 toddlers was selected using accidental sampling from a population of 1,088 toddlers. Data were collected using a self-report questionnaire. The study focused on three key aspects: types of food, quantity of food, and feeding schedules. The results showed that the majority of toddlers (99%) received appropriate feeding patterns, with 98% meeting the standards for types of food, 93% for quantity of food, and 87% for feeding schedules. Overall, the feeding patterns in the study area largely adhered to recommended nutritional standards. However, improvements are needed in feeding schedules to achieve optimal results. It is recommended that community health centers enhance personalized education, such as home visits, to emphasize the importance of breastfeeding and balanced nutrition, while involving families holistically to support appropriate feeding practices.